A Novel Biosorbent From Hardwood Cellulose Nanofibrils Grafted With Poly(m-Aminobenzene Sulfonate) for Adsorption of Cr(VI) - Yu, Yong Ho; An, Liangliang; Bae, Jin Ho; Heo, Ji Won; Chen, Jiansong; Jeong, Hanseob; Kim, Yong Sik (Frontiers in Bioengineering and Biotechnology, 2021)
Cellulose from different lignocellulosic biomass can be used to prepare various materials. In this work, the cellulose nanofibrils were produced from hardwood bleached kraft pulp. Then, a novel biosorbent from cellulose nanofibrils grafted with poly(m-aminobenzene sulfonate) was prepared for effective detoxification and adsorption of Cr(VI) in an aqueous medium. Tempo-oxidized cellulose nanofibrils (TOCN) with a high aspect ratio was used as an adsorbent matrix. Poly(m-aminobenzene sulfonate) (PABS), an amine-rich conductive polymer, was grafted onto TOCN via a successive two-step reaction. The analyses of Fourier-transform infrared (FT-IR) spectroscopy and X-ray photoelectron spectroscopy (XPS) confirmed the successful grafting reaction between TOCNF and PABS. The biosorbent from TOCNF bonded PABS with the nitrogen content of 7.0% was synthesized. It exhibited excellent Cr(VI) adsorption capacity at the solution pH below 3, and almost 100% Cr(VI) can be removed. The adsorption of Cr(VI) on the biosorbent was described by a pseudo-second-order model and obeyed the Langmuir model. The Cr(VI) adsorption capacity of the biosorbent from TOCNF bonded PABS was almost ten times higher than that of TOCNF. It was interesting to note that part of Cr(VI) ions had been reduced to Cr(III) during the adsorption process. It indicated that the biosorbent from TOCNF grafted with PABS could detoxify and adsorb Cr(VI) synchronously.